Estudo da associação entre atributos do solo e produção em tabaco orgânico - Sopelsa, Anderson Monteiro (2013)
The pressure around environmental and social issues related to the cultivation of tobacco, considered one of the main agricultural products in southern Brazil, encouraged the search for cleaner technologies and practices. The production of organic tobacco, therefore, became in the last decade an alternative to reduce the environmental impacts of this crop, eliminating the use of agrochemicals and as response of a growing demand from certain segments of the international consumer market. The objective of this study was to correlate productivity data obtained from the organic production of tobacco, with soil related parameters. The data used were obtained from experiments conducted in the field, in southern Brazil, in 41 organic tobacco crops of integrated producer to a major company of leaf tobacco, following specific technical guidelines for organic production. Correlation and regression analyzes were performed to relate the yield obtained in the years 2011 and 2012 with the chemical and physical properties of soil. The results demonstrated that they have not, for the vast majority of associations evaluated, significant correlations between the chemical and physical properties of soil and yield of organic tobacco. Some results were contrasting the two years of experiment, however, with satisfactory levels for nutrients in most soils, such as potassium and calcium, similar results were achieved in the two years of the experiment. The greatest correlation obtained was between productivity and clay content in the second year of the experiment. Just two years conducting this field experiment were not sufficient to obtain conclusive results, and above all practical conditions applicable to the production of organic tobacco.